Metabolically Unhealthy Phenotype and Its Determinants: A Population-based Study in Southern Iran - Farhang Hooshmand; Vahid Rahmanian; Mohammad Shojaei; Karamatollah Rahmanian (Shiraz University of Medical Sciences, 2023)
Background: The overall prevalence of metabolically unhealthy (MU) phenotype in Iranian adults is a matter of debate. This study aimed to estimate the prevalence and determinants of metabolically unhealthystate in people over 30 years old in the general population in Southern Iran.Methods: In this cross-sectional population-based study, 891 participants aged ≥30 were selected using a multi-stage cluster sampling method. The study examined age, sex, education, marital status, smoking behavior, weight, height, blood pressure, fasting blood sugar, and lipid profiles. MU was defined as the existence of at least two of four constituents of metabolic abnormalities based on ATP III criteria. Data analysis was carried out in Stata version 14. Finally, a logistic regression was performed to identify the risk factors for MU prevalence.Results: The overall prevalence of MU was 49.4%, corresponding to 37.5%, 55.6%, and 60.2% of normal weight, overweight, and obese participants, respectively. MU prevalence significantly increased from 30.6% in participants aged 30-39 years to 69.7% in participants aged 60 years or older. The results of multivariate logistic regression showed that dyslipidemia (OR=2.98, CI95%:2.13-4.16), high LDL (OR=2.73, CI95%:1.77-4.20), obesity (OR=2.83, CI95%:1.84-4.36), overweight (OR=2.13, CI95%:1.53- 2.98), and higher age (OR=1.04, CI95%:1.03-1.05) was positively associated with the MU state.Conclusion: Metabolically unhealthy state is a public health problem in the study area. In terms of public health, screening for obesity and other metabolic disorders should be regularly performed in clinical practice to take appropriate preventive measures.